Analisis Jenis, Jumlah, Mutu Sarapan Terhadap Konsentrasi Belajar Siswa Smp Negeri 29 Palembang - Suci Aji Lestari; Amrina Rosyada (STIKes Hang Tuah Pekanbaru, 2022)
Breakfast is food eaten in the morning, the body needs the energy to carry out activities, breakfast has a positive impact on supporting the activity process from morning to evening. Breakfast is also able to increase enthusiasm, avoid fatigue, increase concentration in learning. This study aims to examine the relationship between breakfast habits and breakfast quality with student concentration at SMP Negeri 29 Palembang. This study uses a cross-sectional approach using a chi-square analysis test. Sample collection was done by a simple random sampling technique. The sample in this study amounted to 97 people with grades 7, 8, 9. The analysis of this study consisted of univariate and bivariate analysis. The results of this study indicate that there is a relationship between breakfast habits (0.002%) and breakfast quality (0.025%) with student concentration at SMP Negeri 29 Palembang. Based on the results of the study, it was shown that the infrequent breakfast habit with poor study concentration showed a proportion of 53 respondents (59.5%), while the poor quality of breakfast with poor study concentration showed a proportion of 32 respondents (91.4%).